Speaker Identification Using Backpropagation Neural Network - Mahmood, Suzan A.; George, Loay E. (Sulaimani Journal for Pure and Applied Sciences, 2008)
In this paper, a neural-based system for speaker identification is investigated. The linear predictive coefficients have been used as a set of descriptors for the speaker data. This set of descriptors is fed to a back propagation neural network for the purpose of speaker identification. Also, it is found that the process of segmenting the audio data into slices has great effect on the identification results, the number and length of slice has major influence on the success of the identification process.
Keywords: Leaner prediction coding; Speaker identification; backpropagation NN